2016
DOI: 10.17235/reed.2016.3943/2015
|View full text |Cite
|
Sign up to set email alerts
|

Primary liposarcoma of the sigmoid presenting as colonic intussusception - A case report

Abstract: Liposarcomas are malignant soft tissue neoplasms usually located in the retroperitoneum, head, neck and extremities. Although secondary invasion of the gastrointestinal tract by retroperitoneal sarcomas is frequent, primary involvement is uncommon. We report a young patient with Crohn's disease in remission presenting with intussusception of the colon due to a primary liposarcoma of the sigmoid. Emergency resection confirmed the diagnosis. The patient remains in remission after five years. This represents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
0
8
0
8
Order By: Relevance
“…Importantly, both these cases showed evidence of a predisposing/co-morbid condition in the form of metabolic syndrome and Crohn disease under medication (azathioprine) 7 , 10. However, the case of Crohn disease did not show any disease activity at the time of surgery 7. Most of the colonic liposarcomas were reported to occur in the cecum or ascending colon similar to the index case, although both the descending colon and sigmoid also can be affected (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, both these cases showed evidence of a predisposing/co-morbid condition in the form of metabolic syndrome and Crohn disease under medication (azathioprine) 7 , 10. However, the case of Crohn disease did not show any disease activity at the time of surgery 7. Most of the colonic liposarcomas were reported to occur in the cecum or ascending colon similar to the index case, although both the descending colon and sigmoid also can be affected (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, Rudnicki et al10 and Fernandes et al7 have described two cases occurring in young individuals. Importantly, both these cases showed evidence of a predisposing/co-morbid condition in the form of metabolic syndrome and Crohn disease under medication (azathioprine) 7 , 10. However, the case of Crohn disease did not show any disease activity at the time of surgery 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They become symptomatic in 75% of cases when their size is larger than 4cm and present with non-specific symptoms such as abdominal pain, constipation, bleeding, perforation and obstruction [ 11 ]. The clinical presentation of intussusception in adults is non-specific and most cases present with a chronic or sub-acute symptoms that are suggestive of chronic constipation [ 7 , 8 , 12 ]. The acute forms are rare and represent less than 20% [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of symptoms is longer in enteric and benign lesions than in malignant and colonic ones [ 13 ]. In our case, intussusception of the sigmoid colon into the rectum is was secondary to a colonic lipoma, however a review of the literature demonstrated that, other lesions in the sigmoid wall are more likely to cause intussusception, such as sigmoid polyp [ 11 ], a sigmoid adenocarcinoma [ 14 , 15 ] and a sigmoid liposarcoma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%